Case Report: Combined Intra-Lesional IL-2 and Topical Imiquimod Safely and Effectively Clears Multi-Focal, High Grade Cutaneous Squamous Cell Cancer in a Combined Liver and Kidney Transplant Patient - Vidovic, Dejan; Simms, Gordon A.; Pasternak, Sylvia; Walsh, Mark; Peltekian, Kevork; Stein, John; Helyer, Lucy K.; Giacomantonio, Carman A. (Frontiers in Immunology, 2021)
Cutaneous squamous cell carcinoma (cSCC) is the second most common non-melanoma skin cancer worldwide, with ever increasing incidence and mortality. While most patients can be treated successfully with surgical excision, cryotherapy, or radiation therapy, there exist a subset of patients with aggressive cSCC who lack adequate therapies. Among these patients are solid organ transplant recipients who due to their immunosuppression, develop cSCC at a dramatically increased rate compared to the normal population. The enhanced ability of the tumor to effectively undergo immune escape in these patients leads to more aggressive tumors with a propensity to recur and metastasize. Herein, we present a case of aggressive, multi-focal cSCC in a double organ transplant recipient to frame our discussion and current understanding of the immunobiology of cSCC. We consider factors that contribute to the significantly increased incidence of cSCC in the context of immunosuppression in this patient population. Finally, we briefly review current literature describing experience with localized therapies for cSCC and present a strong argument and rationale for consideration of an IL-2 based intra-lesional treatment strategy for cSCC, particularly in this immunosuppressed patient population.